Productive Waqf Management Model in Griya Khadijah Airlangga University - Putri, Hamilatul Hasanah; Sukmana, Raditya; Ratnasari, Ririn Tri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
Griya Khadijah is the Rumah Wakaf Amerta Program managed productively by Nazhir Airlangga University in collaboration with Centre for Social Fund Management Airlangga University or PUSPAS UNAIR. By using a qualitative approach with the case study method, through interviews, observation, and documentation, it was found that the Griya Khadijah development management scheme came from temporary waqf assets in the form of buildings, cash waqf, and mudharabah contract which was carried out together with PUSPAS UNAIR and the results of the management of Griya Khadijah were distributed to the UNAIR academic community through the D'Amerta PUSPAS UNAIR distribution program. This scheme benefits many parties, such as scholarship recipients, wakifs, nazhirs, PUSPAS institutions, and the UNAIR academic community. Keywords: Productive Waqf, University Waqf’s Program